Seismic analysis of propped retaining wall - Teoh, Poh Yuan (Nanyang Technological University, 2019)
The single strut propped excavation in the sand is analysed in this project under both static and dynamic conditions. Besides the basic limit equilibrium calculations based on the Eurocode 7 (EC 7), a series of numerical analysis are conducted using the Plaxis 2D finite element software to determine the effects of the soil model, sand friction angle, embedded wall length and earthquake acceleration amplitude on the performance of the retaining system. The horizontal displacement and bending moment of the retaining wall, strut force and lateral earth pressure acting on the wall are compared in the analysis. From the results, the Eurocode 7 limit equilibrium calculations on the maximum wall bending moment and strut force are shown to be more conservative than the results from Plaxis 2D. It is found out that the Hardening Soil with Small-strain (HSS) model is the most suitable soil model which is able to represent the real soil conditions. The results show that when the friction angle of the sand increases, the wall deflection, bending moment and strut force decrease. By keeping all the soil, diaphragm wall and strut properties constant, the wall embedment length is varied to determine the optimum design for this propped excavation. It is observed that the embedded wall length calculated from EC 7 is reasonable. Furthermore, the results have revealed that the seismic load imposes a significant effect on the performance of the propped excavation with the increase in wall deflection, bending moment and strut force compared to the static case. All these parameters increased with the increase of earthquake acceleration amplitude. The average Peak Ground Acceleration is found out to be about 2.6 times of the applied earthquake acceleration. The total lateral earth pressure acting on the retaining wall has also increased with the earthquake acceleration. It is noticed that the effective normal stress and its equivalent force can be related to the earthquake acceleration by a linear relationship.